Historical study of root and the application of ‘vand’ and ‘avand’ suffixes in Persian language - Ahmad Reza Mansoori; Sasan Tahmasbi (مطالعات زبانی و بلاغی)
“Vand” and “Âvand” are two of the main suffixes and dependent morphemes in Persian language which have appeared in the form of “vant” and “âvant” in Avestan. These two suffixes are used in different meaning functions which have transformed through the time. The main purpose of the study is to investigate the derivational form of language. It is considered through historical reasoning and documentations. The original forms of the words which are made from these two suffixes can be found in the names and adjectives of “Pahlavi” and “Avestan”, especially in the regions of Iranian civilization. Although these aren’t enough documentations in order to consider their assessment and functions. The changes which were made in the meaning function and combinational structure of these suffixes are dependent on innate language system and also are affected from historical evolutions. The time of the evolution can be randomly followed from the ancient and Pahlavi languages to the current Persian. The usage of these suffixes was gradually reduced in the middle of Islamic centuries. Their use is basically limited to spoken language and tribes, especially “Lor” ,  “Bakhtiari” and “Lak”.  “Kourd”, “Gil” and “Deylam” families have partly used the suffixes too.